Pengaruh Model Pembelajaran Inkuiri Dengan Metode Eksperimen Terhadap Hasil Belajar Fisika Siswa SMAN 1 Gunungsari Tahun Ajaran 2016/2017 - Sumarni Sahrudin; Wahyudi Wahyudi; Hikmawati Hikmawati (Department of Physics Education, Universitas Mataram, 2019)
This research aims to determine the effect of inquiry learning model with experimental methods towards the result of physics learning of students SMAN 1 Gunungsari academic year 2016/2017. This type of research is a quasi experimental research with pretest-postest control group design. Sampling was done using purposive sampling technique. The results of this research are learning outcomes in the cognitive domain while for the affective domain, and psychomotor as supporting data. The instrument used to measure the learning outcomes in the cognitive domain is an objective test that firstly tested the validity, reliability, differentiation, and degree of difficulty. The average grade of the experimental class's learning result is 68.06 and the control class is 56.25. The result of prerequisite analysis test shows that post test data are normal and homogeneous distributed so that statistic test used is parametric statistic t-test polled varians with t test criterion, and obtained t count equal to 3,95 and t table equal to 2.00 at 5% significant level. Therefore t count is bigger than t table then Ho is rejected and Ha accepted, so there is influence of inquiry learning model with experiment method towards the result of physics learning of students SMAN 1 Gunungsari academic year 2016/2017.